Evaluasi UI Design Pada Prototype Aplikasi “Instix” Menggunakan Metode Sistem Usability Scale - Pratiwi, Ni Putu Dita Ari; Karyawati, Anak Agung Istri Ngurah Eka (Jurnal Nasional Teknologi Informasi dan Aplikasnya; Vol 3 No 2 (2025): JNATIA Vol. 3, No. 2, Februari 2025, 2025)
The success of an application is measured by conducting evaluations to ensure their product is easy to use, understand, and provides a positive experience for users. The Instix application is designed to help business owners centrally manage their products across multiple platforms. This research aims to evaluate the UI design of the Instix application using the System Usability Scale (SUS) method. This research involved 20 participants who were asked to complete certain tasks in the Instix application. Participants then fill out a questionnaire to assess several aspects. The research results show that the evaluation score using the Instix application's Usability Scale (SUS) System method is 87 with the best imaginable category, which shows that this application meets UI and UX quality standards, which can provide an optimal experience in using the application